Reducing Vulnerability and Increasing Resiliency to Climate Change: Learning From Rural Communities - M W Musa; D. F. Omokore (Journal of Agricultural Extension, 2011)
Governments and the international development community generally have responded to various aspects of the global climate change crisis, but questions remain about whether the right actions are being pursued, how best to respond, and what the future holds. Though climate change is a global phenomenon, without doubt, it is not a new phenomenon to people living in rural communities in the tropics and sub-tropics. In Nigeria as well as other parts of Africa, rural people and their communities have over long periods of time built knowledge and developed elaborate strategies and coping mechanism in response to threats imposed by various environmental changes including climate change. Despite their vulnerability and facing greater risks, they have survived and continued to remain resilient. However, the wealth of knowledge in mitigation and adaptive strategies, which ensure the quality and sustainability of their livelihood under changing conditions is yet to be recognized in Nigeria’s climate change policy formulation and implementation. While the crisis of climate change calls for an urgent response from national governments and the international community, debates revolve around the question and possibility of creating conditions and an economy that permits equitable and environmentally sustainable development. This paper highlights the importance of rural people’s contributions as well as insights into the valuable lessons they have to offer in addressing the issue of climate change.